Efeitos psicológicos em vítimas de abuso sexual após audiências criminais com e sem depoimento especial - Skorupa, Marcia Regina (2013)
The present study presents research´s data that aims assess and compare the psychological effects in children and teenagers victims of child sexual abuse that got through two different ways of testimony: the formal testimony and the Special Testimony. The sample was constituted by fifteen participants, divided in experimental group (eight participants that where listened by the Especial Testimony) and control group (seven participants that where not listened by the Especial Testimony). The participants where aged six-eighteen years old. To the research where used two instruments: the Child Behavior Checklist (CBCL), with information from parents ore caregivers and a half-structured interview to assess specific features of testimony (before and after), that was not present at quantitative instrument. The result was analyzed from twenty four CBCL categories: seven of them presents difference between and among the groups: at competence scale subcategory, internalizing problems, externalizing problems, total problems, attention deficit/hyperactivity problems and posttraumatic stress problems. The post-traumatic stress problems had the most notable and discrepant difference. While the control group presented five of seven participants with score, only two of eight experimental group participants had the same result. Analyzing the interview, the experimental group obtained the major number of participant with positive experiences resulting from testimony, as relief sense and acknowledgment for been “heard”; in control group, was observed only participants that, according to their mothers, kept their “normal” behavior after the testimony, or had negative experiences (as been nervous, scared, crying), nevertheless, without positive experiences. The data analysis appoints to a tendency that Especial Testimony reduces the psychological consequences that has accurred from child victims of sexual abuse testimony.